Pedagogical Potential Of "Event" Technology In Personal Formation (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this article, issues related to the pedagogical potential of "Event" technology in personal protection are considered. As a technology for organizing children's extracurricular and free time, the pedagogical potential of the "Event" technology is that it is of great importance in the implementation of children's personal requests, in revealing the qualities and characteristics of the person, in their development and formation. studied